The Effect of Virtual and Augmented Reality Technologies for Volcano Eruption Disaster Management in The Build of Environments - Shane, Nathanael Marvel; Putri, Novita Surya; Fahmi, Akhmad Yanuar (Journal of Rural Community Nursing Practice, 2023)
Panjen Hamlet is located near Raung Mountain, categorized as an active volcano, and prevention activity is very common among the people of Panjen Hamlet nowadays. Volcano eruption disaster management is one of the requirements for people who live near the volcano eruption area. Due to that condition, adequate disaster management knowledge, equipment, and mental readiness are needed. This study aimed to determine the effect of Virtual & Augmented Reality Technologies (VART) on volcano eruption disaster management among Karang Taruna community adolescent members. The design of this study used a pre-experimental design with total sampling techniques. The samples in this study were 20 respondents with statistical analysis using the Wilcoxon test. The study results obtained a mean pre-test value of 2.70 with a standard deviation of 0.470, while the mean post-test value was 3.0 with a standard deviation of 0.000. The results were assigned after the data were analyzed using the Wilcoxon test in SPSS version 26. Sig = 0.014 < 0.5 were obtained, which means Virtual & Augmented Reality Technologies (VART) influenced volcano eruption disaster management. Giving VART as a new learning method plays an essential role in increasing the level of understanding in Karang Taruna community adolescent members to prepare the readiness of the respondent when faced with a volcano eruption disaster.